Evaluation of change in tumor stiffness measured by acoustic radiation force impulse imaging for early prediction of response to neoadjuvant chemotherapy in breast cancer. Issue 5 (30th March 2022) - Mahadevan, Gowtham Sembagounden Valasu; Chakkalakkoombil, Sunitha Vellathussery; Kayal, Smita; Dharanipragada, Kadambari; Toi, Pampa Ch.; Ananthakrishnan, Ramesh
Abstract: Objectives: In this study, the role of change in tumor stiffness between pre‐ and post‐two cycles of neoadjuvant chemotherapy (NACT) measured by Acoustic Radiation Force Impulse (ARFI) imaging for predicting the response to NACT in breast cancer was analyzed. Methods: Fifty‐two adult women with biopsy‐proven locally advanced breast cancer and early‐stage breast cancer who received NACT followed by either modified radical mastectomy or breast conservation surgery were included in the study. Tumor stiffness represented by shear wave velocity (SWV) in meter per second by ARFI imaging was measured before and after two cycles of NACT. Participants were categorized into responders and nonresponders based on pathological response assessment from the postoperative specimen. The association of change in tumor stiffness between pre‐ and post‐two cycles of NACT with final pathological response status was assessed. Results: The mean change in SWV before and after completion of two cycles of NACT was 0.42 ± 0.16 and 0.17 ± 0.11 m/s in responders and nonresponders, respectively, and this difference was proven to be statistically significant ( p  < 0.001) suggesting that tumors that exhibit a larger reduction in tumor stiffness, respond better. An SWV reduction cut‐off of 0.295 m/s between baseline and post‐two cycles of NACT was also arrived at, which can discriminate between responders and nonresponders with a sensitivity and specificity of 88% and 83%, respectively. Conclusion: Difference in tumor stiffness measured by ARFI imaging before and after two cycles of chemotherapy can be used as a reliable early predictor of response to chemotherapy in breast cancer. Abstract : In our prospective longitudinal observational study of 52 women with biopsy‐proven locally advanced and early‐stage breast cancer who received neoadjuvant chemotherapy (NACT) before surgery, we analyzed the role of difference in tumor stiffness represented by shear wave velocity before NACT and after two cycles of NACT measured by ARFI imaging as a predictor of final pathological response status. We found a significant association between the two and also arrived at an SWV difference cutoff value of 0.295 m/s between pre‐ and post‐two cycles of NACT which can reliably discriminate between responders and nonresponders.